Mechanical Characterisation Of Sawdust And Chipwood-Filled Epoxy Composite - Seyajah, Norhisham (2008)

(untitled)
Natural fibre are increasingly being used as reinforcement in commercial thermoset due to their low cost and renewable nature. In this research the composite of epoxy with sawdust and chip wood untreated wood fibre content 14% by weight as a filled were studied and waste wood obtained from the timber industry. The highest tensile strength valued for sawdust is 28.917 MPa and chip wood is 21.951 MPa, compare with epoxy if self is 16.307 MPa. Meanwhile the highest flexural strength values for sawdust is 0.468 MPa, and chip wood is 0.596 MPa, compare with epoxy it self is 0.645 MPa. However in addition the good trend in elongation at break of epoxy composite with sawdust and chip wood due to the dispersion of the individual fibre as the fibre contents was different size in the matrix. It is also that some matrix materials adhere to the surface of the pull out fibre indicating a good bond and interfacial adhesion between the matrix and the fibre.Further testing, using scanning electron microscopy (SEM) micrographs on tensile of sawdust epoxy composite showed very little fibre pull out and splitting, and for tensile of chip wood epoxy composite showed although there is a bigger contact surface between filler and matrix but the adhesion is no good. Meanwhile the flexural of sawdust epoxy composite showed the poor adhesion and there are a void around the sawdust particle, and for flexural of chip wood epoxy composite showed cavities clearly indicate the poor interfacial adhesion between the epoxy matrix polymer.